Active site conformational changes upon reaction intermediate biotinyl‐5'‐AMP binding in biotin protein ligase from Mycobacterium tuberculosis. (22nd April 2014) - Ma, Qingjun; Akhter, Yusuf; Wilmanns, Matthias; Ehebauer, Matthias T.
Abstract Protein biotinylation, a rare form of post‐translational modification, is found in enzymes required for lipid biosynthesis. In mycobacteria, this process is essential for the formation of their complex and distinct cell wall and has become a focal point of drug discovery approaches. The enzyme responsible for this process, biotin protein ligase, substantially varies in different species in terms of overall structural organization, regulation of function and substrate specificity. To advance the understanding of the molecular mechanism of biotinylation in Mycobacterium tuberculosis we have biochemically and structurally characterized the corresponding enzyme. We report the high‐resolution crystal structures of the apo‐form and reaction intermediate biotinyl‐5'‐AMP‐bound form of M. tuberculosis biotin protein ligase. Binding of the reaction intermediate leads to clear disorder‐to‐order transitions. We show that a conserved lysine, Lys138, in the active site is essential for biotinylation.